Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.22437/gentala.v4i2.8437
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Penilaian Portofolio Di Sekolah Dasar

Abstract: This portfolio assessment has been widely applied in primary schools in Indonesia. In practice portfolio assessment has been widely used for the teacher certification process. This study aims to describe the implementation of portfolio assessment and describe the results of the implementation of portfolio assessment in elementary schools. The approach in this study uses a qualitative approach. While the type of research used in this study is the basic theory. This research was carried out at Muara Bulian 80 / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
3
0
7
Order By: Relevance
“…Teachers should not use one of the dominant assessments, but are expected to adapt various assessment models. The use of various forms of assessment is expected to increase motivation and learning outcomes, as well as to maximize the development of psychological aspects [7]. For example, students who are only evaluated using a type of test, of course the orientation of developing their thinking patterns only refines the theoretical aspects and does not develop their skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers should not use one of the dominant assessments, but are expected to adapt various assessment models. The use of various forms of assessment is expected to increase motivation and learning outcomes, as well as to maximize the development of psychological aspects [7]. For example, students who are only evaluated using a type of test, of course the orientation of developing their thinking patterns only refines the theoretical aspects and does not develop their skills.…”
Section: Discussionmentioning
confidence: 99%
“…This becomes an obstacle in portfolio assessment because one important component in portfolio assessment is the rubric of assessment which will later convert scores into student learning outcomes. Furthermore, the results of other studies also indicate that so far portfolio assessments conducted by primary school teachers substantially depend on private worksheet books which, according to some teachers, are the mainstay of teachers in learning today [7]. In addition, another empirical fact was found that in one of the favorite schools that had used portfolio assessment as a form of assessment, it was also not entirely successful.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan tiga aspek penilaian yang meliputi afektif, kognitif dan psikomotor. Akan tetapi dari hasil penelitian data yang diperoleh peneliti belum lengkap, guru belum memasukkan semua data penilaian kedalam lembar portofolio peserta didik Meskipun tidak mengembangkan kriteria penilaian, guru dapat memberi skor terhadap tugas yang telah dikerjakan peserta didik (Kuntarto & Gustina, 2019).…”
Section: Pembahasanunclassified
“…Namun dalam pelaksanaannya sebagian guru masih belum menggunakan instrumen penilaian dengan baik ketika penilaian aspek keterampilan, sebagian guru terkadang hanya menilai hasil belajar peserta didik aspek keterampilan dengan perasaan (Lius et al, 2019). Pada beberapa mata pelajaran guru hanya melaksanakan ujian tertulis berbentuk soal objektif dan isian untuk mengetahui hasil belajar peserta didik tanpa memperhatikan keterampilan proses peserta didik dalam pembelajaran (Kuntarto & Gustina, 2019).…”
unclassified
“…Penilaian portofolio bertujuan untuk merefleksi suatu pekerjaan yang telah di kerjakan oleh peserta didik (Efendi et al, 2017;Kuntarto & Gustina, 2019).…”
Section: Pendahuluanunclassified